PSIKOLOGI KEBERLANJUTAN SEKOLAH PEKERJA ANAK DI SEKTOR BATIK - Siti Mumun Muniroh (JURNAL PENELITIAN, 2011)
The aim of this study was to know the psychological dynamics of child labour in Batik sector in Pekalongan. This case study research applied interview, observation and documentation for collecting data. The findings of this research show that school breakout child labour generally motivated to work only to earn, whereas the school child labour, more motivated by pity feeling of their parents. The children labour affective condition has different ways in order to face the problems of school continuity. Some felt disappointed on failure to continue their school, some felt so-so, and some others felt happy because of school duties-free. Generally, child labour was excited when they help their parents or when they work in the owner of the interprise. They also felt proud because they could help out their parentsí burdens. The school breakout child labour tend to have no any desires for coming back to their school because of feeling happy in working. It differs with the school children, which still have an expectation to continue to the higher education and have aspiration.